2019
DOI: 10.1039/c8tb03181a
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic poly(vinyl alcohol)–chitosan as a new type of highly efficient hemostatic sponge with blood-triggered swelling and high biocompatibility

Abstract: Synthetic poly(vinyl alcohol)–chitosan as a new type of highly efficient hemostatic sponge with blood-triggered swelling and high biocompatibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 38 publications
2
46
0
Order By: Relevance
“…Despite the porous and three-dimensional structure of sponges promoting blood clotting, soft and injectable materials such as hemostatic hydrogels have attracted research interest within the past decade. Previous studies have reported that the hemostatic hydrogels possess the unique ability to adequately fill and adhere to irregular wounds, contributing to more efficient hemorrhage control [ 11 , 12 , 13 ]. Moreover, soft hemostatic hydrogels could be easily removed through water or phosphate buffered saline (PBS), which can be carried out to reduce secondary wound bleeding [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the porous and three-dimensional structure of sponges promoting blood clotting, soft and injectable materials such as hemostatic hydrogels have attracted research interest within the past decade. Previous studies have reported that the hemostatic hydrogels possess the unique ability to adequately fill and adhere to irregular wounds, contributing to more efficient hemorrhage control [ 11 , 12 , 13 ]. Moreover, soft hemostatic hydrogels could be easily removed through water or phosphate buffered saline (PBS), which can be carried out to reduce secondary wound bleeding [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genipin/PVA/chitosan buccal patch (Formulation 4) and a commercial chitosan‐based dressing were placed into glass tubes at 37°C and the mixture of blood and citrate dextrose was placed on the samples. The resulting samples were examined by inverting the tubes until the blood flow completely stopped and the clotting time was recorded 45 …”
Section: Methodsmentioning
confidence: 99%
“…The model of skin defect: [21,22] the anesthetized SD rats were fixed on the operating table, after the hair of their back was shaved, a full-thickness defect with a diameter of 10 mm was built on the back. The observed animals were randomly divided into the hydrogel experimental group and the blank control group (n = 5).…”
Section: Animal Experimental Studymentioning
confidence: 99%